ANALYSIS OF THE CURRENT STATUS OF THE POLICE ORGANIZATION’S ROLE IN ENSURING ECONOMIC SECURITY - Altansukh Norov (International Journal of Innovative Technologies in Social Science, 2025)
Economic security encompasses a nation’s economic stability, independence, and safeguarding against external influences. The Mongolian Police have been actively engaged in activities aimed at maintaining national security, preventing crime, preserving public order, and ensuring public safety. While the police is fulfilling their legal responsibilities to uphold economic security, there is a lack of coordination among organizations, as well as a shortage of skilled personnel, advanced technology, and equipment. Therefore, it is imperative to assess the current role of the police in economic security and explore ways to enhance their involvement in safeguarding economic interests. This study investigates the current role of Mongolia’s police organization in safeguarding economic security, focusing on combating financial crimes and money laundering. By analyzing seven years of crime data (2017-2023) and using SWOT methodology, the research highlights significant challenges in law enforcement’s ability to effectively address economic threats. The SWOT analysis identifies organizational strengths such as experienced personnel and established monitoring systems, but also highlights critical weaknesses in technological infrastructure, human resource capacity, and inter-agency coordination. External opportunities for improvement include international cooperation and legal framework enhancements, while threats stem from evolving criminal tactics, technological advancements by perpetrators, and political interference. In conclusion, the study emphasizes that despite active involvement in economic security initiatives, Mongolia’s police encounter significant challenges in personnel training, technological resources, and organizational coordination. To effectively combat sophisticated economic crimes and safeguard national economic interests, enhanced international collaboration, modernized investigative tools, improved legal frameworks, and strengthened inter-agency cooperation are essential.